PET (Polyethylene Terephthalate) composite material as well as preparation method and application thereof

By adding toughener and sarin resin with specific functional groups to the PET material and regulating the molecular weight distribution, the problems of slow forming and poor thermal oxygen aging performance of PET materials are solved, and rapid molding and impact resistance are improved, which has expanded the Its application scope.

CN119242001AActive Publication Date: 2025-01-03KINGFA SCI & TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411437053.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-03
Estimated Expiration
2044-10-15

AI Technical Summary

Technical Problem

During use, PET materials have problems such as low crystallization temperature, slow crystallization rate, slow molding, low notch impact strength and intolerance of thermal oxygen aging, which limits their application range.

Method used

By adding toughener with glycidyl methacrylate functional groups to the PET resin and sarin resin, combined with an appropriate proportion of plasticizers, a microcrosslinked product is formed to improve the toughness and heat-resistant oxygen performance of the material, and through regulation The weight average molecular weight and molecular weight distribution index of PET resin achieve rapid molding and impact resistance.

Benefits of technology

It has achieved the improvement of rapid molding, impact resistance and thermal oxygen aging performance of PET materials, shortened the processing cycle and improved the long-term use stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005085318550000051
    Figure BDA0005085318550000051
  • Figure BDA0005085318550000061
    Figure BDA0005085318550000061
  • Figure BDA0005085318550000062
    Figure BDA0005085318550000062
Patent Text Reader

Abstract

The invention discloses a PET (Polyethylene Terephthalate) composite material which comprises the following components in parts by weight: 80 parts of PET resin; 13-23 parts of a rapid prototyping modifier; the rapid prototyping modifier comprises a toughening agent with a glycidyl methacrylate functional group, surlyn resin and a plasticizer in a weight ratio of (2-5): 1: (0.29-0.72). According to the invention, the toughening agent with glycidyl methacrylate functional groups, the sarin resin and the plasticizer are compounded, such that advantages of rapid molding, impact resistance, and thermo-oxidative aging resistance can be simultaneously realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer materials, and in particular to a PET composite material and a preparation method and application thereof. Background Art

[0002] Polybutylene terephthalate (PET) is widely used in various fields, such as electronic appliances, home appliances and automobiles, due to its excellent mechanical strength, solvent resistance, electrical properties and heat resistance. However, PET has obvious disadvantages during use, including low crystallization temperature, slow crystallization rate leading to slow molding, low notched impact strength, intolerance to thermal oxygen aging, etc., which makes its processing cycle long, not resistant to falling, and powdering after long-term use, limiting its application range. Summary of the invention

[0003] The purpose of the present invention is to overcome the above technical defects and provide a PET composite material with rapid prototyping, impact resistance and good thermal oxygen aging resistance.

[0004] The present invention also aims to provide a preparation method and application of the PET composite material.

[0005] The present invention is achieved through the following technical solutions:

[0006] A PET composite material, comprising the following components by weight:

[0007] PET resin 80 parts;

[0008] 13-23 parts of rapid prototyping modifier;

[0009] The rapid prototyping modifier is a toughening agent with a glycidyl methacrylate functional group: a sarling resin: a plasticizer in a weight ratio of (2-5): 1: (0.29-0.72);

[0010] The weight average molecular weight of the PET resin is 20000-26000, and the molecular weight distribution index is 1.4-1.7.

[0011] The reaction of PET with a large weight average molecular weight and a toughening agent can greatly improve toughness, while the effect is not obvious for PET with a small weight average molecular weight. The present invention selects a molecular weight distribution index of 1.4-1.7 because low molecular weight PET can play a nucleation role, increase molding speed and improve heat and oxidation resistance. When the distribution index is too narrow, the proportion of components with large molecular weight is high, resulting in a decrease in crystallization performance; when the distribution index is too wide, the proportion of components with small molecular weight is high, which is not conducive to toughening.

[0012] The weight average molecular weight and molecular weight distribution index were tested using GPC equipment, and the test method was as follows: mobile phase: hexafluoroisopropanol, flow rate: 0.35 mL / min, column temperature: 55°C, RI detector temperature: 54°C, cleaning solvent: isopropanol, calibration substance: polymethyl methacrylate (PMMA).

[0013] The PET resin of the present invention can be a commercial product or a self-made raw material. The preparation method is as follows: terephthalic acid and ethylene glycol are used as raw materials, and the activity difference between antimony catalyst and titanium catalyst is utilized (reference document "Application of titanium composite catalyst in PET synthesis") to prepare PET with different molecular weight distribution indexes, and solid phase viscosity increasing method is used at the same time, and the weight average molecular weight and molecular weight distribution index of PET are controlled by adjusting the viscosity increasing time. Preparation process: ethylene glycol and terephthalic acid (molar ratio 1.25-1.35:1) are put into a reaction kettle, the amount of antimony catalyst (such as antimony acetate) is 200-300ppm, the titanium catalyst (such as DH-HyTi titanium-based catalyst) is 20-30ppm, the esterification temperature is 240-260℃, the time is 3-5h, and the polycondensation temperature under vacuum conditions is 260-280℃, the time is 4-8h. Solid phase viscosity increasing process: vacuum degree 80-120Pa, temperature 210-230℃, time 10-20h.

[0014] The present invention has no particular limitation on the melt index of the PET resin. When the melt index is within the range of 20-40 g / min (test method is ISO 1133, condition is 270° C. / 2.16 kg), the purpose of the present invention can be achieved.

[0015] Preferably, the weight ratio of toughener with glycidyl methacrylate functional group: sarling resin: plasticizer is (2.5-3.5):1:(0.4-0.6).

[0016] The melt index range of the glycidyl methacrylate functional toughener is 0.5-20 g / 10 min, and the test conditions are 190° C. and 2.16 kg.

[0017] The sarling resin is an ethylene-acrylic acid metal salt ionomer, and the metal salt can be sodium ion, zinc ion, etc., preferably sodium ion.

[0018] The toughening agent with glycidyl methacrylate functional group is selected from at least one of a glycidyl methacrylate copolymer toughening agent and a glycidyl methacrylate grafted toughening agent; the glycidyl methacrylate copolymer toughening agent is selected from at least one of an ethylene-methyl acrylate-glycidyl methacrylate copolymer and an ethylene-butyl acrylate-glycidyl methacrylate copolymer, wherein the weight content of glycidyl methacrylate is 4-9wt%, preferably 7.5-8.5wt%; the glycidyl methacrylate grafted toughening agent is selected from an ethylene-octene copolymer grafted glycidyl methacrylate, wherein the weight content of glycidyl methacrylate is 0.3-2.8wt%, preferably 2.5-2.8wt%.

[0019] The method of grafting ethylene-octene copolymer with glycidyl methacrylate (GMA) is as follows: a single-screw extruder, a twin-screw extruder, an internal mixer and other processing equipment are used to react at a temperature of 150-200° C. to complete the melt grafting of the ethylene-octene copolymer component. Specifically, taking the internal mixer as an example, GMA is added to the ethylene-octene copolymer in a molten state, the reaction temperature is 150-200° C., the rotation speed is 200-500 rpm, the concentration of the GMA monomer is controlled, and the initiator diisopropylbenzene peroxide and dibenzoyl peroxide can be selected, and the amount of the initiator is 0.05-0.3% of the total weight of the grafted monomer.

[0020] Preferably, the melt index of the ethylene-octene copolymer is in the range of 1-5 g / 10 min (test standard is ISO 1133, condition is 190° C. / 2.16 kg).

[0021] The plasticizer is selected from polyether ester plasticizers with a flash point of 250-350°C and ester plasticizers with a flash point of 250-350°C; preferably, the plasticizer is selected from polyether ester plasticizers with a flash point of 250-350°C.

[0022] The ester plasticizer with a flash point of 250-350° C. is selected from at least one of benzene polyester plasticizers, polyester plasticizers, and epoxy soybean oil plasticizers.

[0023] The polyester plasticizer may be an aliphatic dibasic acid ester plasticizer.

[0024] The benzene polyester plasticizer can be selected from tetraoctyl pyromellitic acid and trimellitic acid ester.

[0025] By weight, the invention further comprises 0-2 parts of auxiliary agents, wherein the auxiliary agents are selected from at least one of lubricants and antioxidants.

[0026] The lubricant may be one or more of aliphatic carboxylic acid esters, erucic acid amide, ethylene bis stearamide, montan esters, polyethylene wax, and oxidized polyethylene wax;

[0027] The antioxidant may be a hindered phenol antioxidant, a phosphite antioxidant, an organic sulfur antioxidant, or a composite antioxidant system composed of several of them;

[0028] The preparation method of a PET composite material comprises the following steps: uniformly mixing the components according to a ratio, extruding and granulating the components through a twin-screw extruder to obtain the PET composite material, wherein the temperatures of the screws of the twin-screw extruder from a feed port to a die are 230-240°C, 240-250°C, 240-250°C, 240-250°C, 260-270°C, 250-260°C, 250-260°C, 240-250°C, 240-250°C, and 240-250°C, respectively, and the screw speed is 250-400rpm.

[0029] The application of PET composite materials is used to prepare household appliance housings, electronic and electrical component housings, etc.

[0030] The present invention has the following beneficial effects:

[0031] The present invention mainly achieves the advantages of rapid prototyping, impact resistance and thermal oxygen aging resistance by compounding a toughening agent with a glycidyl methacrylate functional group: a sarling resin: a plasticizer. This is because the toughening agent with a glycidyl methacrylate functional group undergoes a micro-crosslinking reaction with the sarling resin. When the two are in a specific ratio, a crosslinked product that can absorb a large amount of energy is formed. Under the condition of thermal oxygen, the crosslinking reaction is further intensified, so that the material properties are maintained; at the same time, the sarling resin and the plasticizer are compounded to promote the nucleation and crystallization of PET, thereby achieving rapid prototyping, impact resistance and thermal oxygen aging resistance. DETAILED DESCRIPTION

[0032] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0033] The sources of raw materials used in the present invention are as follows:

[0034] PET resin A: weight average molecular weight 21613, molecular weight distribution index 1.42, homemade;

[0035] PET resin B: weight average molecular weight 23326, molecular weight distribution index 1.56, homemade;

[0036] PET resin C: weight average molecular weight 24544, molecular weight distribution index 1.51, homemade;

[0037] PET resin D: weight average molecular weight 24278, molecular weight distribution index 1.68, homemade;

[0038] PET resin E: weight average molecular weight 23885, molecular weight distribution index 2.17, homemade;

[0039] PET resin F: weight average molecular weight 16432, molecular weight distribution index 1.63, homemade;

[0040] PET resin G: weight average molecular weight 28442, molecular weight distribution index 1.46, homemade;

[0041] PET resin H: weight average molecular weight 21013, molecular weight distribution index 1.33, homemade;

[0042] Toughener A-1: ​​ethylene-methyl acrylate-glycidyl methacrylate copolymer, the weight content of glycidyl methacrylate is 6wt%, Sumitomo, BF-7M;

[0043] Toughener A-2: ethylene-methyl acrylate-glycidyl methacrylate copolymer, the weight content of glycidyl methacrylate is 8wt%, Arkema, AX8900;

[0044] Toughening agent A-3: ethylene-methyl acrylate-glycidyl methacrylate copolymer, the weight content of glycidyl methacrylate is 3wt%, Ketong, KT-33;

[0045] Toughener B: ethylene-butyl acrylate-glycidyl methacrylate copolymer, the weight content of glycidyl methacrylate is 5wt%, DuPont, PTW;

[0046] Toughener C-1: ethylene-octene copolymer grafted with glycidyl methacrylate, the weight content of glycidyl methacrylate is 0.3wt%, homemade;

[0047] Toughener C-2: ethylene-octene copolymer grafted with glycidyl methacrylate, the weight content of glycidyl methacrylate is 1.2wt%, homemade;

[0048] Toughening agent C-3: ethylene-octene copolymer grafted with glycidyl methacrylate, the weight content of glycidyl methacrylate is 2.5wt%, homemade;

[0049] Toughener C-4: ethylene-octene copolymer grafted with glycidyl methacrylate, the weight content of glycidyl methacrylate is 2.8wt%, homemade;

[0050] Toughening agent C-5: ethylene-octene copolymer grafted with glycidyl methacrylate, the weight content of glycidyl methacrylate is 0.1wt%, homemade;

[0051] Surlyn resin 1: DuPont surlyn 8920, sodium salt;

[0052] Surlyn resin 2: DuPont surlyn 9910, zinc salt;

[0053] Plasticizer A: benzene polyester plasticizer, Kunshan Huayi, TOPM, flash point is 265℃;

[0054] Plasticizer B: aliphatic dibasic acid ester plasticizer, Zhangjiagang DIC Chemical Co., Ltd., W-2340-S, flash point 270°C;

[0055] Plasticizer C: trimellitate plasticizer, Zhangjiagang DIC Chemical Co., Ltd., W-700-D, flash point 263°C;

[0056] Plasticizer D: Epoxidized soybean oil plasticizer, Guangzhou Haierma Vegetable Oil Co., Ltd., HM-01AD, flash point 290℃;

[0057] Plasticizer E: polyether ester plasticizer, Aidico (China) Investment Co., Ltd., RS-735, flash point 252°C;

[0058] Plasticizer F: aliphatic dibasic acid ester plasticizer, United Chemical Technology Co., Ltd., UN899, flash point 224°C;

[0059] Antioxidant: antioxidant 1010 and antioxidant 168, compound ratio 1:3, commercially available;

[0060] Lubricant: PETs, aliphatic carboxylic acid esters, commercially available.

[0061] Various test methods:

[0062] (1) Molding evaluation: With reference to the cup-shaped mold used in Chinese patent CN202020371834.4, 100 molds were continuously injected. No mold sticking was allowed during the injection molding process. The molding cycle time was recorded and the average molding cycle time was calculated in seconds.

[0063] (2) Toughness evaluation: Injection mold a 100*100*3 mm sample, fix the sample in a device, drop a 1 kg iron ball from a height of 1 m onto the sample, and observe whether the sample cracks. Test 10 times. If there is one crack, it is judged as failed.

[0064] (3) Thermal oxidative aging tensile strength retention rate: According to ISO 527-2, the tensile strength G1 of the injection molded specimen is tested, and the unit is MPa. The specimen is placed in a 120°C thermal oxidative aging oven for 2000 hours, and the tensile strength G2 is tested again, and the retention rate = G2 / G1*100%.

[0065] Table 1: Content of each component (parts by weight) and test results of PET composite materials in Examples 1-6

[0066]

[0067]

[0068] It can be seen from Examples 1-4 and Comparative Examples 5 / 6 / 8 / 9 that when the weight average molecular weight and molecular weight distribution index of the PET resin are not within the range of the present invention, the impact resistance and thermal oxygen aging resistance are poor.

[0069] Table 2: Content of each component (parts by weight) and test results of PET composite materials of Examples 7-12

[0070]

[0071]

[0072] It can be seen from Examples 1 / 7-12 that the weight content of glycidyl methacrylate in the glycidyl methacrylate copolymer toughening agent is preferably 7.5-8.5wt%; and the weight content of glycidyl methacrylate in the ethylene-octene copolymer grafted with glycidyl methacrylate is 2.5-2.8wt%.

[0073] Table 3: Content of each component (parts by weight) and test results of PET composite materials of Examples 13-17

[0074]

[0075] It can be seen from Examples 1 / 13 that sodium ions are preferred for sarling resin, which has better heat aging resistance.

[0076] It can be seen from Examples 1 / 14-17 that when the plasticizer is preferably a polyether ester plasticizer, the molding cycle is the shortest and the heat and oxygen aging resistance is better.

[0077] Table 4: Content of each component (parts by weight) and test results of PET composite materials in Examples 18-21

[0078]

[0079] It can be seen from Examples 1 / 18-21 and Comparative Example 1 / 2 that when the ratio of the rapid prototyping modifier is preferably selected, the molding cycle is shorter and the heat-oxidative aging resistance is better. If the ratio of the rapid prototyping modifier is not within the scope of the present invention, the technical effects of short molding cycle, good toughness and good heat-oxidative aging resistance cannot be achieved at the same time.

[0080] Table 5: Comparative Examples 1-7 PET composite material component content (parts by weight) and test results

[0081]

[0082]

[0083] It can be seen from Comparative Examples 3 / 4 that if the weight content of glycidyl methacrylate in the toughening agent is too low, the toughness is poor and the oxygen aging resistance is poor.

[0084] It can be seen from Comparative Example 7 that if the flash point of the plasticizer is too low, the molding cycle is too long.

[0085] Table 6: Comparative Examples 8-9 PET composite material component content (parts by weight) and test results

[0086]

[0087] It can be seen from Comparative Examples 8 / 9 that when the weight average molecular weight and molecular weight distribution of the PET resin are not within the scope of the present invention, the molding cycle is long and the thermal oxidative aging tensile strength retention rate does not reach 50%.

Claims

1. A PET composite material, characterized in that: By weight, it includes the following components: PET resin 80 parts; 13-23 parts of rapid prototyping modifier; The rapid prototyping modifier is a toughening agent with a glycidyl methacrylate functional group: the weight ratio of sarling resin to plasticizer is (2-5):1:(0.29-0.72); the weight average molecular weight of the PET resin is 20000-26000, and the molecular weight distribution index is 1.4-1.

7.

2. The PET composite material according to claim 1, characterized in that: The weight ratio of toughener with glycidyl methacrylate functional group: sarrin resin: plasticizer is (2.5-3.5):1:(0.4-0.6).

3. The PET composite material according to claim 1, characterized in that: The sarling resin is an ethylene-acrylic acid metal salt ionomer, and the metal salt is at least one of sodium ion and zinc ion, preferably sodium ion.

4. The PET composite material according to claim 1, characterized in that: The toughening agent with glycidyl methacrylate functional group is selected from at least one of a glycidyl methacrylate copolymer toughening agent and a glycidyl methacrylate grafted toughening agent; the glycidyl methacrylate copolymer toughening agent is selected from at least one of an ethylene-methyl acrylate-glycidyl methacrylate copolymer and an ethylene-butyl acrylate-glycidyl methacrylate copolymer, wherein the weight content of glycidyl methacrylate is 4-9wt%, preferably 7.5-8.5wt%; the glycidyl methacrylate grafted toughening agent is selected from an ethylene-octene copolymer grafted with glycidyl methacrylate, wherein the weight content of glycidyl methacrylate is 0.3-2.8wt%, preferably 2.5-2.8wt%.

5. The PET composite material according to claim 1, characterized in that: The plasticizer is selected from polyether ester plasticizers with a flash point greater than or equal to 250°C and ester plasticizers with a flash point greater than or equal to 250°C; preferably, the plasticizer is selected from polyether ester plasticizers with a flash point greater than or equal to 250°C.

6. The PET composite material according to claim 5, characterized in that: The ester plasticizer with a flash point greater than or equal to 250° C. is selected from at least one of benzene polyester plasticizers, polyester plasticizers, and epoxy soybean oil plasticizers.

7. The PET composite material according to claim 1, characterized in that: By weight, the invention further comprises 0-2 parts of auxiliary agents, wherein the auxiliary agents are selected from at least one of lubricants and antioxidants.

8. The method for preparing the PET composite material according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: uniformly mixing the components according to a proportion, extruding and granulating through a twin-screw extruder to obtain a PET composite material, wherein the temperatures of the screws of the twin-screw extruder from a feed port to a die are 230-240°C, 240-250°C, 240-250°C, 240-250°C, 260-270°C, 250-260°C, 250-260°C, 240-250°C, 240-250°C, and 240-250°C, respectively, and the screw speed is 250-400rpm.

9. Use of the PET composite material according to any one of claims 1 to 7, characterized in that: Used to prepare housings for household appliances and housings for electronic and electrical components.

Citation Information

Patent Citations

  • Thermal aging resistant PET modified material and its preparation method

    CN102337010A

  • Fast-crystallization glass fiber reinforced PET (polyethylene terephthalate) composition and preparation method thereof

    CN115011081A

  • PBT composite material, and preparation method and use therefor

    WO2024139930A1